2022
DOI: 10.1177/07334648221084998
|View full text |Cite
|
Sign up to set email alerts
|

Care v. Caring: Obligation, Duty, and Love Among Latino Alzheimer’s Family Caregivers

Abstract: The number of Latinos living with Alzheimer’s disease is projected to grow. Latinos currently make one-fifth of U.S. family caregivers. In this paper, we explore the cultural scripts and gendered practice of care in Latino families in relation to the underutilization of services to persons with Alzheimer’s disease and related dementias. We conducted interviews with 24 Latino caregivers in Miami-Dade, Florida representing six Latin American countries of origin. Interviews were analyzed using a grounded theory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The included studies reported facilitators of willingness to access HCBS as referrals from trusted healthcare providers, family, or friends (Horsfall et al, 2016; Ketchum et al, 2022; Koehn et al, 2019), cultural beliefs (Blix & Munkejord, 2022; Motta-Ochoa et al, 2021), availability of culturally diverse or tailored services (Biswas et al, 2022; Browne et al, 2014; Horsfall et al, 2016; Willis et al, 2016; Xiao et al, 2015), culturally acceptable supports (Arora et al, 2020), and caregiving crises (Benedetti et al, 2013; Willis et al, 2016). The reported barriers were beliefs of caregivers, care recipients, and their community about caregiving and dementia (Armstrong et al, 2022; Arora et al, 2020; Benedetti et al, 2013; Berdai Chaouni & De Donder, 2019; Biswas et al, 2022; Browne & Braun, 2017; Casado et al, 2015; Casado & Lee, 2012; Crist & Speaks, 2011; Czapka & Sagbakken, 2020; Giuntoli & Cattan, 2012; Greenwood et al, 2016; Haralambous et al, 2014; Herat-Gunaratne et al, 2020; Horsfall et al, 2016; Ketchum et al, 2022; Koehn et al, 2019; Lee & Smith, 2012; Liu & McDaniel, 2015; Martinez et al, 2022; Martinez & Acosta Gonzalez, 2022; Motta-Ochoa et al, 2021; Nielsen et al, 2020; Nkimbeng et al, 2022; Pound & Greenwood, 2016; Shanley et al, 2012; Strudwick & Morris, 2010; Sun et al, 2014; Williams et al, 2021; Willis et al, 2016; Xiao et al, 2015), and previous negative individual or collective experiences with health and social services (…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The included studies reported facilitators of willingness to access HCBS as referrals from trusted healthcare providers, family, or friends (Horsfall et al, 2016; Ketchum et al, 2022; Koehn et al, 2019), cultural beliefs (Blix & Munkejord, 2022; Motta-Ochoa et al, 2021), availability of culturally diverse or tailored services (Biswas et al, 2022; Browne et al, 2014; Horsfall et al, 2016; Willis et al, 2016; Xiao et al, 2015), culturally acceptable supports (Arora et al, 2020), and caregiving crises (Benedetti et al, 2013; Willis et al, 2016). The reported barriers were beliefs of caregivers, care recipients, and their community about caregiving and dementia (Armstrong et al, 2022; Arora et al, 2020; Benedetti et al, 2013; Berdai Chaouni & De Donder, 2019; Biswas et al, 2022; Browne & Braun, 2017; Casado et al, 2015; Casado & Lee, 2012; Crist & Speaks, 2011; Czapka & Sagbakken, 2020; Giuntoli & Cattan, 2012; Greenwood et al, 2016; Haralambous et al, 2014; Herat-Gunaratne et al, 2020; Horsfall et al, 2016; Ketchum et al, 2022; Koehn et al, 2019; Lee & Smith, 2012; Liu & McDaniel, 2015; Martinez et al, 2022; Martinez & Acosta Gonzalez, 2022; Motta-Ochoa et al, 2021; Nielsen et al, 2020; Nkimbeng et al, 2022; Pound & Greenwood, 2016; Shanley et al, 2012; Strudwick & Morris, 2010; Sun et al, 2014; Williams et al, 2021; Willis et al, 2016; Xiao et al, 2015), and previous negative individual or collective experiences with health and social services (…”
Section: Resultsmentioning
confidence: 99%
“…Values around caregiving such as filial piety, defined as cultural norms and values that dictate how children treat their parents, (Bedford & Yeh, 2021), influenced decisions not to access services. Caregivers described the influence of filial piety on caregiving as either positive, for example, a meaningful experience (Armstrong et al, 2022; Arora et al, 2020; Crist & Speaks, 2011; Czapka & Sagbakken, 2020; Herat-Gunaratne et al, 2020; Horsfall et al, 2016; Martinez & Acosta Gonzalez, 2022; Martinez et al, 2022; Motta-Ochoa et al, 2021; Strudwick & Morris, 2010; Williams et al, 2021) or negative, for example, an obligation (Benedetti et al, 2013; Berdai Chaouni & De Donder, 2019; Browne & Braun, 2017; Casado & Lee, 2012; Czapka & Sagbakken, 2020; Herat-Gunaratne et al, 2020; Koehn et al, 2019; Lee & Smith, 2012; Martinez & Acosta Gonzalez, 2022; Nielsen et al, 2020; Shanley et al, 2012; Willis et al, 2016). Caregivers interviewed in some studies believed that the care they provided was superior to professional care due to their dedication and intimate knowledge of the care recipient (Benedetti et al, 2013; Crist & Speaks, 2011; Greenwood et al, 2016; Martinez et al, 2022; Martinez & Acosta Gonzalez, 2022; Nkimbeng et al, 2022; Strudwick & Morris, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, some people may search for detailed information on a topic, whereas others may seek brief or no information at all (Ford et al, 2002; Friis et al, 2003; Leydon et al, 2000). In Latino communities, stigma can be associated with the diagnosis of Alzheimer’s disease or related dementias, receiving mental health services, and placing aging parents in assisted living facilities (Beyene et al, 2002; Cabrera et al, 2021; Fripp & Carlson, 2017; Martinez & Acosta Gonzalez, 2022). This can influence the amount of information Latinos seek about these topics.…”
mentioning
confidence: 99%